2019
DOI: 10.1111/rec.12978
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the soil microbial community and carbon‐use efficiency following development of Vochysia guatemalensis tree plantations in unproductive pastures in Costa Rica

Abstract: This study shows that Vochysia guatemalensis tree plantations were associated with enhanced soil biotic and abiotic characteristics in previously cleared forests in the northern zone of Costa Rica, suggesting the possible use of this practice as a restoration strategy for local land owners. Soil samples from a primary forest, secondary forest, and a 13‐year‐old plantation of V. guatemalensis had greater relative abundances of DNA sequences of microbial genera critical for carbon‐use (C‐use) efficiency (i.e. th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Changes in the composition of the soil fungal communities associated with wood rot, lignin degradation, degradation of other complex C compounds, and associated changes in Biomass C and C-use efficiency, have been observed in soils following various types of forest disturbances [ 20 , 38 , 84 ], and as such, these should be considered as possible indicators of soil ecosystem recovery. In our study, we found greater MPS values of the CCD/WRT/Lignin genera Calonectria , Trichoderma , and Xylaria in the Pre-compared to the Post-Hurricane soils, and greater MPS values the CCD/WRT/Lignin genera Cryptococcus , Geotrichum , Gliocladiopsis and Mortierella in the Post- compared to the Pre-Hurricane soils in all three forest habitats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the composition of the soil fungal communities associated with wood rot, lignin degradation, degradation of other complex C compounds, and associated changes in Biomass C and C-use efficiency, have been observed in soils following various types of forest disturbances [ 20 , 38 , 84 ], and as such, these should be considered as possible indicators of soil ecosystem recovery. In our study, we found greater MPS values of the CCD/WRT/Lignin genera Calonectria , Trichoderma , and Xylaria in the Pre-compared to the Post-Hurricane soils, and greater MPS values the CCD/WRT/Lignin genera Cryptococcus , Geotrichum , Gliocladiopsis and Mortierella in the Post- compared to the Pre-Hurricane soils in all three forest habitats.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising, as, in general, this would require a serendipitous event for it to happen On November 24, 2016, Hurricane Otto hit the forests in the Northern Zone of Costa Rica providing just such a serendipitous opportunity to conduct a before and after study in the exact same long-term forest plots. Permanent plots established previously in three primary forest types within the Maquenque National Wildlife Refuge in the Northern zone of Costa Rica, an Upland Forest Type, Lowland Forest Type, and Riparian Forest Type, and used for various studies [ 33 38 ], with soil samples collected for a project in the summer of 2016. Upon arrival at the sites in summer 2017, we found that all plots in all three forest types had been hit hard by Otto, significantly decreasing the percent canopy cover by about 40 to 70%, and littering the forest floor with young leaf litter and large amounts of woody debris.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental DNA was extracted from each of the 18 composite soil samples using three 0.33 g replicate sub-samples for a total of 1 g for each composite soil sample using the MoBio PowerSoil DNA Isolation Kit (MO BIO Laboratories Inc., Carlsbad, CA, USA) and according to the manufacturer’s protocol. The concentration and purity (A 260 /A 280 ratio) of extracted soil DNA were determined prior to downstream analyses using a NanoDrop 1000 spectrophotometer (ThermoFisher Scientific, Waltham, MA) and all eDNA was stored at − 80 °C, as has been done in previous studies 55 , 69 , 70 .…”
Section: Methodsmentioning
confidence: 99%
“…The 2nd PCR was made following the same protocol as aforementioned except for 30 cycles were used for PCR. All PCR products were visualized on 1.5% agarose gels to confirm successful amplification by the presence of fluorescent bands, as has been done previously 55 , 69 , 70 . All PCRs were done using Eppendorf Mastercycler ep gradient S thermalcyclers and negative control reactions (no DNA template) were included in all experiments, and all generated soil amplicons plates were dual indexed and pooled into a single tube and sequenced in several Illumina MiSeq runs using a V2 MiSeq sequencing kit (500 cycles—250 × 2) (FC-131-1002 and MS-102-2003).…”
Section: Methodsmentioning
confidence: 99%
“…On November 24, 2016, Hurricane Otto hit the forests in the Northern Zone of Costa Rica providing the serendipitous opportunity to conduct just such a before and after study in the exact same long-term forest plots. These plots had been permanently established previously in three primary forest types within the Maquenque National Wildlife Refuge in the Northern zone of Costa Rica, [34], as well as for the soil samples collected for a project in the summer of 2016. Upon arrival at the sites in summer 2017, we found that all plots in all three forest types had been hit hard by Otto, significantly decreasing the percent canopy cover by about 40 to 70%, and littering the forest floor with young leaf litter and large amounts of CWD.…”
Section: Introductionmentioning
confidence: 99%